PEMBERDAYAAN MASYARAKAT DAN MANAJEMEN KESEHATAN LINGKUNGAN MELALUI INOVASI PAPAN EDUKASI SAMPAH DI DESA WONGGAHU, KECAMATAN PAGUYAMAN - Delvin Sairullah; Hetfil Dai; Mirfat Laneto; Salmawati Abas; Shilvy Indriani Bata; Anisa Abdullah; Amnatia Abdullah (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Waste management remains a critical issue facing rural communities, including those in Wonggahu Village, Paguyaman District. Low public awareness of the importance of environmental cleanliness has led to increased pollution and a decline in public health. This community service initiative aims to empower the community through innovative waste education boards as a means of information and behavior change. The program involved field observation, needs analysis, educational content design, and the creation and installation of boards in strategic locations. The results demonstrate increased public awareness of the importance of properly sorting and disposing of waste. This program demonstrates students' concrete contribution to creating a clean, healthy, and sustainable environment through education and community participation.